RESEARCH ON SPEED AND PRESSURE CONTROL STRATEGY OF STABLE SWITCH ABOUT FOREPOLING EQUIPMENT - LUAN LiJun; ZHAO HuiMeng; XIE Miao; LIU ZhiXiang (Jixie qiangdu)
Taking into account the operational principle of forepoling equipment,and as the target to improving support efficiency and reducing the disturbance on the roof in the process of supporting,a kind of speed and pressure composition control method was presented.The control method adopts the constant pump driven directly by servo motor to replace the traditional electro-hydraulic proportional valve,and the variable structure algorithm based on the fuzzy sliding mode was used as control strategy.Theoretical analysis and experimental results show that,compared with the traditional speed and pressure control method,the control method presented in the paper can reduce concussion on the roof in the process of switching from speed control to pressure control,and can improve support efficiency.Research findings can provide a theoretical basis for the development and control strategy of forepoling equipment.